Probiotics and Isoflavones as a Promising Therapeutic for Calcium Status and Bone Health: A Narrative Review - Iskandar Azmy Harahap; Joanna Suliburska (Foods, 2021)
Probiotics have potential clinical effects for treating and preventing osteoporosis. Meanwhile, isoflavones have attracted much attention due to their ability to prevent postmenopausal symptoms. Research has established that probiotics and isoflavones can regulate hormones, immune cells, and the gastrointestinal system, acting as links in the gut–bone axis. However, combining the effects of probiotics and isoflavones on calcium status and bone health is a more novel and a still-evolving research area. Lactobacillus and Bifidobacterium are the foremost strains that influence bone health to a significant extent. Among the isoflavones, daidzein, genistein, and the metabolites of genistein (such as equol) stimulate bone formation. It can be concluded that probiotics and isoflavones promote bone health by regulating calcium uptake, gut microbiota, and various metabolic pathways that are associated with osteoblast activity and bone formation. Nevertheless, further experiments of probiotics and isoflavones are still necessary to confirm the association between calcium bioavailability and bone health.